Understanding the Concept of Stanya and its Need in Context to Breastfeeding - Tanwar, Kiran; Tanwar, Ankur Kumar (International Research Journal of Ayurveda & Yoga, 2022)
One of the most fundamental requirements of human life is food. The nutritional requirements vary from childhood through age. Infant mortality is greater in developing countries, such as India, due to a lack of sufficient nourishment for children. As a result, it is critical to provide sufficient nourishment to children. Milk is the most important food for children since it not only gives them energy but also helps them grow and develop properly throughout this time. Even during the Vedic Period, breast milk was thought to be a great meal for newborns. The Rigveda recommends breastfeeding after delivery while reciting Mantras. Under the topic of jatakarma, several ayurvedic literatures demonstrate the importance of breastfeeding. One of the updhatu of rasa is stanya, or breast milk, according to Ayurvedic literature. Breast milk has several health benefits for both the mother and the child. Breastfeeding should begin as soon as the baby is born. Breastfeeding is the most effective approach to care for a newborn. Breast milk is the ideal diet for them, in addition to the overpowering attachment it fosters. The present review focused on the concept of stanya or breast milk mentioned in Ayurvedic literatures and its need in the present era.